Adaptation of left ventricular diastolic function to pregnancy: a systematic review and meta-analysis. Issue 10 (October 2021) - de Haas, Sander; Spaanderman, Marc E.A.; van Kuijk, Sander M.J.; van Drongelen, Joris; Mohseni, Zenab; Jorissen, Laura; Ghossein-Doha, Chahinda
Abstract : Objective: To meta-analytically determine the adaptation of left ventricular diastolic function (LVDF)-indices to singleton normotensive pregnancies. Methods: Literature was retrieved from PubMed and Embase. We included studies that reported a nonpregnant reference measurement and LVDF indices (mitral inflow signals, left atrial volume and tissue Doppler measurements). Mean differences between pregnant and reference measurements and weighted means of absolute values were calculated using a random-effects model. Results: We included 34 eligible studies. Normotensive pregnancies were characterized by an initially larger increase in the passive left ventricular filling (E-wave peak velocity, 13%) compared to active left ventricular filling during diastole (A-wave peak velocity, 6%) resulting in a 16% increase of the E/A ratio in the first trimester. The E/A ratio progressively decreased during advancing gestation to −18% at term, resulting from stabilizing E-wave peak velocity and increased A-wave peak velocity. The E/e′ ratio was increased between 22 and 35 weeks (a maximal increase of 13%) in normotensive pregnancy. Left atrial volume (LAV) progressively increased from 15 weeks onwards with a maximal increase of 30% between 36 and 41 weeks. Conclusion: LVDF in normotensive pregnancy was improved in the first trimester after which LVDF progressively worsened. Large-scale studies in normotensive and hypertensive complicated pregnancies are needed for a more precise insight into LVDF changes during pregnancy. Abstract : Supplemental Digital Content is available in the text